Signaling Pathways Governing the Caspofungin Paradoxical Effect in Aspergillus fumigatus - Nicolas Papon (American Society for Microbiology, 2020)
ABSTRACT Aspergillus fumigatus is responsible for a wide range of diseases affecting several million people worldwide. Currently, a few families of antifungals are available to fight aspergillosis, and we are facing a worrisome increase in resistance to azoles, the drugs used for both first-line treatment and prophylaxis of invasive aspergillosis. In this context, some of the latest antifungals, i.e., echinocandins, have gained attention. Even though acquired resistance to echinocandins is yet uncommon in A. fumigatus clinical isolates, some strains exhibit another characteristic that relies on their capacity to grow at suprainhibitory echinocandin concentrations in vitro. This intriguing phenomenon, especially observed with caspofungin and now referred to as the caspofungin paradoxical effect (CPE), relies on molecular mechanisms that were hitherto little understood. Here, we discuss the recent key findings of Valero and colleagues published in mBio (C. Valero, A. C. Colabardini, J. Chiaratto, L. Pardeshi, et al., mBio 11:e00816-20, 2020, https://doi.org/10.1128/mBio.00816-20) that will allow a better understanding of the complex regulatory pathway involved in governing the response of A. fumigatus to caspofungin.